Improving Research Capacity at Universitas Diponegoro, Indonesia - Utama, Yos Johan; Ambariyanto, Ambariyanto (Journal of Sustainability Perspectives, 2021)
As a higher education institution with a vision to become a research university, programs and activities related to research are Universitas Diponegoro main concern. Research is one of the three main pillars of higher education in Indonesia, apart from education and community service. Besides that, as a state university, its development is also influenced by central government policies. Currently, Undip is a state university with legal status and has wide autonomy. This paper explains research programs, activities and challenges that still need to be addressed in the future. To increase research capacity at Diponegoro University, there are five main programs, namely: 1. Increasing the capacity of human resources; 2. Improvement of facilities and supporting facilities; 3. Increasing the availability of research funds, 4. Collaboration and 5. Creating a conducive environment to research development at universities. Based on the application of the five programs, there has been a substantial increase in a research capacity, especially when viewed from indicators of international scientific publications, and an increase in the number of patents obtained. But there are still many challenges that need to be overcome, including the increase in the citation of published papers and the utilization of patent by industries.